2015
DOI: 10.1177/0003489415583330
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Macroglossia Due to Lymphatic Malformation With Sirolimus

Abstract: This article presents a novel approach to the treatment of lymphatic malformation of the tongue using sirolimus, which appears to be safe and effective for the management of complex cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…One prospective nonrandomized study and 17 retrospective studies described the treatment of lymphatic malformations with oral sirolimus. 14,19,26,32,41,48,56,61,[64][65][66][67][68][69][70][71][72][73] The median age was 12.8 years (0-34 years); 20% of patients were younger than 1 year, and 90% were younger than 18 years. Nonspecified decrease in lesion size was reported in 77.8% patients, partial response in 22.2%, complete response in 3.7%, improvement of pleural effusion in 9.9%, decrease of skin exudate and vesicles in 16.5%, and improvement of pain in 4.9%.…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…One prospective nonrandomized study and 17 retrospective studies described the treatment of lymphatic malformations with oral sirolimus. 14,19,26,32,41,48,56,61,[64][65][66][67][68][69][70][71][72][73] The median age was 12.8 years (0-34 years); 20% of patients were younger than 1 year, and 90% were younger than 18 years. Nonspecified decrease in lesion size was reported in 77.8% patients, partial response in 22.2%, complete response in 3.7%, improvement of pleural effusion in 9.9%, decrease of skin exudate and vesicles in 16.5%, and improvement of pain in 4.9%.…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…Rapamycin was selected for our patient due to his critical situation. This decision was made based on what it had been published in the literature (Adams et al, ; Alemi, Rosbe, Chan, & Meyer, ; Fogel, Hill, & Teng, ; Hammill et al, ; Yesil et al, ). Among favorable reports in rapamycin therapy, Alemi et al () demonstrated two patient's airway obstruction improvement, and Yesil et al () described a case with lymphatic vascular anomaly and macroglossia, practically solved in 9 months of treatment with oral rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have focused on the role of PI3K activation and inhibition in vascular endothelial cells, it is important to keep in mind that sirolimus is an immunosuppressant, and it may have greater than one mechanism of action in LM. Clinical response of HNLM or LM associated syndromes/disorders such as Gorham‐Stout disease, kaposiform hemangioendothelioma, combined lymphatico‐venous malformation, pulmonary lymphangectasia, generalized lymphangiomatosis, and LM of the tongue to sirolimus has varied . Literature to date does not yet distinguish which patients are the best candidates for sirolimus and what true benefits it has.…”
Section: Therapy For Head and Neck Lymphatic Malformations Based On Mmentioning
confidence: 99%
“…Clinical response of HNLM or LM associated syndromes/disorders such as Gorham-Stout disease, kaposiform hemangioendothelioma, combined lymphatico-venous malformation, pulmonary lymphangectasia, generalized lymphangiomatosis, and LM of the tongue to sirolimus has varied. [26][27][28][29][30][31][32][33] Literature to date does not yet distinguish which patients are the best candidates for sirolimus and what true benefits it has. A phase 2 trial analyzed the outcomes after empiric use of sirolimus in patients with complicated LM throughout the body.…”
Section: Therapy For Head and Neck Lymphatic Malformations Based On Mmentioning
confidence: 99%